Kazakh language media content as a factor in strengthening national identity - Petrov Б.С.; Esdauletov А.О.; Saidikarimov А.Ф. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
In the context of globalization, the issue of national identity is becoming increasingly important, one of the factors in the formation of which is the linguistic component. In Kazakhstan, despite the indicators of population growth and the number of people who speak Kazakh, the lack or poor quality of media content in the state language remains an urgent problem of the information space. The article examines the state of Kazakh-language media content within the framework of the State Program for the implementation of language policy in the Republic of Kazakhstan for 2020-2025, where the task is to create successful media products for the dissemination of Kazakh-language content. To achieve this goal, a survey of residents aged 10 to 50 years old who speak the Kazakh language was conducted. Respondents were asked questions about the daily use of content in the Kazakh language, their assessment of the availability and quality of media content in the Kazakh language, including on the Internet, as well as how it affects their views. The correlation was revealed that residents of cities and regions where the majority use Kazakh in everyday life, estimate the level of accessibility of content on the Internet in Kazakh is lower than those regions where Russian is mainly used. This is the answer to the question of how the program is being implemented to expand the scope of the state language in the conditions of digitalization. Thus, the results of the survey allow us to draw conclusions about the lack of media content in the Kazakh language, which directly affects the self-identification of Kazakhstanis and the formation of Kazakhstan’s national identity as a whole.